Multi-channel information dissemination for disaster evacuees – the case of the 2016 Kumamoto Earthquake in Japan - John W. Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2018)
This study examines factors that affect disaster evacuees' usage of different media in a multi-channel media environment, which means that people can receive similar content from multiple media channels. Using the 2016 Kumamoto Earthquake in Japan as the case study, we find that that multi-channel information dissemination is indeed an effective means to provide information to disaster evacuees. Specifically, it is found that traditional broadcast media and Internet media can complement each other rather than displacing. In addition, Internet media such as online TV, video streaming websites and Internet radio are effective alternatives to traditional broadcast media for providing official information to victims in severely damaged areas, which broadcast media might not be available.
Keywords: 330; Multi-channel information dissemination; disaster risk reduction; media consumption across platforms